Is traditional milk marketing and processing viable and efficient? An empirical evidence from Assam, India - Kumar, Anjani; Staal, Steven J. (2010)
Integrated food supply chains serving urban areas are the fastest growing and most visible market phenomenon, yet small scale milk market agents and chains supplying fresh milk and traditionally processed dairy products still play a very large role in most of the developing countries. This study estimates the costs and returns of milk marketing and processing, identifies the drivers for participation in high value milk processing and value addition and estimates the cost efficiency and its determinants in the traditional milk sector in Assam. The study observed that raw milk trading and processing offers good opportunities for income generation to small scale milk traders and processors. The raw milk marketing and trading is reasonably efficient and has the potential for continued dominance in spite of emerging integrated food supply chains.